1993
DOI: 10.2527/1993.712467x
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: an improved method for extraction and quantification of toxic phenethylamines from Acacia berlandieri

Abstract: N-methyl-beta-phenethylamine (NMPEA) has been previously identified as the toxin causing locomotor ataxia in sheep and goats grazing the browse plant, Acacia berlandieri. We describe a simplified procedure for extraction and quantification of naturally occurring beta-phenethylamines from this Acacia species. Dried, ground plant tissue was extracted (1:20 wt/vol) with 1% glacial acetic acid and filtered. The filtrate was passed through a high-sulfonated polymeric solid-phase extraction (SPE) tube, which retaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The NMT was originally believed to be one of the toxins in Acacia species and other plants that caused locomotor ataxia in sheep and goats (Pemberton et al ., ; Clement et al ., ). However, subsequent studies have shown that it is not responsible for toxicity in ruminants (Bourke et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The NMT was originally believed to be one of the toxins in Acacia species and other plants that caused locomotor ataxia in sheep and goats (Pemberton et al ., ; Clement et al ., ). However, subsequent studies have shown that it is not responsible for toxicity in ruminants (Bourke et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Amine analyses were conducted at the Texas A&M Agricultural Experiment Station in Uvalde, Texas following extraction and analysis procedures of Pemberton et al (1993). Briefly, 1 g of ground material was added to 20 ml 1 % glacial acetic acid and extracted overnight on a rotary shaker followed by filtering through filter paper to remove solid plant tissue.…”
Section: Methodsmentioning
confidence: 99%
“…When consumed at even low concentrations, phenolic amines can have severe physiological effects on domestic livestock, such as reduced reproductive performance (Forbes et al 1993, 1994, Vera-Avila et al 1996, 1997). Forbes et al (1995) found that tyramine and N-methyl-phenethylamine (NMP) concentrations significantly increased in regrowth guajillo after simulated browsing.…”
Section: Introductionmentioning
confidence: 99%